Quality Of Public Services In The Religious Court Of Garut Regency In The Covid-19 Pandemic Era - Syarah Nursyamsiah (Fakultas Ilmu Sosial dan Ilmu Politik - Universitas Garut, 2023)
The Covid-19 pandemic is a non-natural disaster that has attacked various sectors, including the economic sector. Economic problems caused a massive recession and impacted the stability of household life. Domestic conflicts arise due to the non-fulfillment of the family's basic needs, leading to divorce. In the end, people flocked to the Religious Courts to register their divorce proceedings. When someone wants to file a divorce trial, they will be met with a service officer. Based on this case, researchers are interested in researching the quality of public services at the Garut Regency Religious Court during the Covid-19 pandemic era. The research method used is a quantitative method with a SERVQUAL approach. The sample used was 100 respondents and was taken using the Bernoulli calculation technique. Next, the researcher uses tabulation techniques to present the data. Then, the research shows that most respondents agree on all the SERVQUAL attributes on the questionnaire sheet. Respondents stated that the service quality of the Garut District Religious Court was good regarding the SERVQUAL dimension. Another conclusion is that most parties filing for divorce are the wives. Keywords: Public Services; SERVQUAL.